Beyond a sacrificial spirituality: Enhancing flourishing pastoral ministers - Dillen, Annemie (HTS teologiese studies, 2017)
This contribution explains the value of self-giving and critically questions the discourse on self-sacrifice in relation to ministerial spirituality. In practice, what others may describe as self-sacrifice may be experienced by a care-giver as an adequate form of self-giving inspired by the Christian vocation, without any praise for one’s own deeds, without any overestimation of the heroic character of one’s own giving. An inherent danger in the concept of self-sacrifice is a closedness to critically assessing the balance of power in one’s own relationships. In this sense, theologians are asked to use the concept self-sacrifice with caution, as the theological language may inspire people, ideas and the general discourse further than intended.